Comparing the Species Diversity of Birds at Gunung Gading National Park, Mount Jagoi and Mount Singai, Sarawak. - Nur Afini Amelia, Benz Azraai (Universiti Malaysia Sarawak (UNIMAS), 2015)
Avifauna surveys were conducted at Gunung Gading National Park, Lundu from 18th until 24th October 2014 and 14th until 19" January 2015. The main objective was to study the species composition of birds in Gunung Gading, Mount Jagoi and Mount Singai. This study also compared the diversity of avifauna in Gunung Gading and Mount Jagoi also Mount Singai. Primary data was obtained from the field sampling while secondary data were obtained from previous study. A total of twenty mist nets were deployed for six days in each site, from 0600 to 1800 hour daily. A total of 97 individuals from 31 species and 13 families were recorded at Gunung Gading National Park. A total of 298 individuals comprising 53 species from 22 families were recorded at Mount Jagoi; while there were 66 individuals comprising 18 species from 11 families were recorded at Mount Singai. The most dominant species in these three areas was Little Spiderhunter (Arachnothera longirostra), while the dominant families were Nectariidae, Pycnonotidae and Timaliidae. The result showed that bird community at Mount Jagoi was richer and significantly diverse that Gunung Gading and Mount Singai.